Effects of Marquandomyces marquandii SGSF043 on the Germination Activity of Chinese Cabbage Seeds: Evidence from Phenotypic Indicators, Stress Resistance Indicators, Hormones and Functional Genes - Xu Zheng; Yuxia Huang; Xinpeng Lin; Yuanlong Chen; Haiyan Fu; Chunguang Liu; Dong Chu; Fengshan Yang (Plants)
In this study, the effect of Metarhizium spp. M. marquandii on the seed germination of cabbage, a cruciferous crop, was investigated. The effects of this strain on the seed germination vigor, bud growth and physiological characteristics of Chinese cabbage were analyzed by a seed coating method. The results showed the following: (1) The coating agent M. marquandii SGSF043 could significantly improve the germination activity of Chinese cabbage seeds. (2) The strain concentration in the seed coating agent had different degrees of regulation on the antioxidase system of the buds, indicating that it could activate the antioxidant system and improve the antioxidant ability of the buds. (3) When the concentration of M. marquandii SGSF043 was 5.6 × 106 CFU/mL (average per grain), the effect of M. marquandii SGSF043 on the leaf hormones Indole Acetic Acid (IAA), Gibberellic Acid (GA) and Abscisic Acid (ABA) of Chinese cabbage seedlings was significantly higher than that of other treatment groups, indicating that the strain could optimize the level of plant hormones. (4) M. marquandii SGSF043 could induce the expression of stress-resistance-related genes in different tissue parts of Chinese cabbage and improve the growth-promoting stress resistance of buds. This study showed that M. marquandii SGSF043 could not only improve the germination vitality of Chinese cabbage seeds but also enhance the immunity of young buds. The results provide a theoretical basis for the application potential of Metarhizium marquandii in agricultural production.